Efisiensi Alokatif Usahatani Jeruk Siam di Kabupaten Sambas - Sugara, Aga; Kurniati, Dewi; Suharyani, Anita (Journal Galung Tropika, 2021)
Siamese oranges are the primary commodity of agricultural products in Tebas District. However, instability of the cost of capital in farming can cause uncertainty in the selling price of the product at each time of production. Therefore, this study focuses on the influence of production factors and allocative efficiency of Siamese citrus farming in Sambas Regency. Data were obtained from 88 Siamese orange farmers in Tebas Sungai Village who were selected by random sampling method using the Slovin formula. The research location was chosen based on the number of farmers and Siamese orange production among other villages in Tebas District, Sambas Regency. The coefficient of determination of 0.698 is calculated by linear regression analysis so that it shows the attachment between the two kinds of variables, while 0.302 comes from the external model. The F test shows the calculated F value > F table of 2.58> 2.04, which indicates the level of Siamese citrus production is simultaneously and significantly affected by the variables of land use, seed selection, and use of labor. The efficiency test found that the variables of land use and seed selection were efficient with a value of NPMx=1.